PERAN KOPERASI DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA DI KOPERASI UNIT DESA BALE YOTRO DESA BELOYANG - Tri Handayani; Avelius Dominggus Sore; Yunita Astikawati (JURKAMI : Jurnal Pendidikan Ekonomi, 2020)
This research is against the backdrop of no change in the welfare of cooperative members of bale yotro village unit beloyang village. The aim of this research is explaining the factors that influence the cooperative in increasing the prosperity of bale yotro village cooperative unit’s member, beloyang village. Research uses qualitative methods with data collection techniques namely observation, interview and documentation. The results of this research: 1) cooperative plays a major role in enhancing theprosperityofcooperative members, 2) the efforts of cooperatives in increasing the prosperity of their members by developing cooperativebusiness units, providing the needs are needed by members, establishing relationships and cooperation with cooperative partners to achieve the goals of cooperative work programs, and making innovations and opportunities for cooperative members, 3) driving factors and inhibition in improving the welfare of members.AbstrakRiset ini dilatarbelakangi tidak adanya perubahan kesejahteraan anggota koperasi unit desa bale yotro desa beloyang. Penelitian ini bertujuan untuk mendeskripsikan faktor pendorong dan penghambat koperasi  dalam meningkatkan kesejahteraan anggota di koperasi unit desa bale yotro desa beloyang. Penelitian menggunakan metode kualitatif dengan teknik pengumpulan data yaitu observasi,wawancara dan dokumentasi. Hasil penelitian: 1) koperasi sudah berperan  besar dalam meningkatkan kesejahteraan anggota. 2) upaya koperasi dalam meningkatkan kesejahteraan anggota adalah mengembangkan  unit usaha yang dimilki koperasi dengan menyediakan  kebutuhan yang dibutuhkan oleh anggota, menjalin relasi dan kerjasama dengan mitra kerja yang mendukung program kerja koperasi untuk mencapai tujuan, dan melakukan inovasi serta membaca peluang untuk meningkatkan kesejahteraan anggota.3) faktor pendorong dan penghambat dalam meningkatkan kesejahteraan anggota